2012
DOI: 10.1371/journal.pgen.1003006
|View full text |Cite
|
Sign up to set email alerts
|

New Partners in Regulation of Gene Expression: The Enhancer of Trithorax and Polycomb Corto Interacts with Methylated Ribosomal Protein L12 Via Its Chromodomain

Abstract: Chromodomains are found in many regulators of chromatin structure, and most of them recognize methylated lysines on histones. Here, we investigate the role of the Drosophila melanogaster protein Corto's chromodomain. The Enhancer of Trithorax and Polycomb Corto is involved in both silencing and activation of gene expression. Over-expression of the Corto chromodomain (CortoCD) in transgenic flies shows that it is a chromatin-targeting module, critical for Corto function. Unexpectedly, mass spectrometry analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 67 publications
2
38
0
Order By: Relevance
“…Despite the consensus that ribosomal subunits are inactive in the nucleus, it has been previously reported that many ribosomal proteins (RPs), rRNA, and some translation factors (including eIF5b) seem to associate with nascent transcripts at polytene chromosomal transcription sites in Drosophila (Brogna et al 2002;Coleno-Costes et al 2012;Rugjee et al 2013). These observations suggest the presence of ribosomal subunits at these sites.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the consensus that ribosomal subunits are inactive in the nucleus, it has been previously reported that many ribosomal proteins (RPs), rRNA, and some translation factors (including eIF5b) seem to associate with nascent transcripts at polytene chromosomal transcription sites in Drosophila (Brogna et al 2002;Coleno-Costes et al 2012;Rugjee et al 2013). These observations suggest the presence of ribosomal subunits at these sites.…”
Section: Introductionmentioning
confidence: 99%
“…For example the effect of RpL11 on cMyc is specific for RpL11 since other RPs do not show similar activities. There is also evidence that some RPs might bind chromatin-associated proteins in Drosophila and regulate transcription (Ni et al, 2006; Coleno-Costes et al, 2012). Tri-methylated RpL12, for example, interacts with the Corto protein at the chromosomes and regulates a set of heat response and RP genes (Coleno-Costes et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…kis mutants present ectopic wing veins, and increase ectopic vein phenotypes of mutants affecting the BAP complex component SNR1 [22], [24], [29]. Finally, loss of the ETP Corto [30], [31] induces ectopic veins and enhances ectopic vein phenotypes of several TrxG gene mutants [24], [32], implicating corto in control of vein vs intervein fate. Interestingly, Corto associates with ERK and its scaffold protein MP1 on chromatin, potentially linking ERK signaling to transcriptional regulation mediated by TrxG and ETPs [15], [32], [33].…”
Section: Introductionmentioning
confidence: 91%